Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Hydrogenase‐ and outer membrane c ‐type cytochrome‐facilitated reduction of technetium(VII) by Shewanella oneidensis MR‐1 - Matthew J. Marshall; Andrew E. Plymale; David W. Kennedy; Liang Shi; Zheming Wang; Samantha B. Reed; Alice C. Dohnalkova; Cody J. Simonson; Chongxuan Liu; Daad A. Saffarini; Margaret F. Romine; John M. Zachara; et al. (Environmental Microbiology, 2008)
Summary Pertechnetate, 99 Tc(VII)O 4 – , is a highly mobile radionuclide contaminant at US Department of Energy sites that can be enzymatically reduced by a range of anaerobic and facultatively anaerobic microorganisms, including Shewanella oneidensis MR‐1, to poorly soluble Tc(IV)O 2(s) . In other microorganisms, Tc(VII)O 4 – reduction is generally considered to be catalysed by hydrogenase. Here, we provide evidence that although the NiFe hydrogenase of MR‐1 was involved in the H 2 ‐driven reduction of Tc(VII)O 4 – [presumably through a direct coupling of H 2 oxidation and Tc(VII) reduction], the deletion of both hydrogenase genes did not completely eliminate the ability of MR‐1 to reduce Tc(VII). With lactate as the electron donor, mutants lacking the outer membrane c ‐type cytochromes MtrC and OmcA or the proteins required for the maturation of c ‐type cytochromes were defective in reducing Tc(VII) to nanoparticulate TcO 2 ·nH 2 O (s) relative to MR‐1 or a NiFe hydrogenase mutant. In addition, reduced MtrC and OmcA were oxidized by Tc(VII)O 4 – , confirming the capacity for direct electron transfer from these OMCs to TcO 4 – . c ‐Type cytochrome‐catalysed Tc(VII) reduction could be a potentially important mechanism in environments where organic electron donor concentrations are sufficient to allow this reaction to dominate.

A Reliable Field-Inoculation Method for Identifying Aflatoxin-Resistant Maize - Yudong Zhang; Janet G. Simonson; Guilin Wang; Manjit S. Kang; Hershel F. Morris (Cereal Research Communications, 1998)